Digital Leadership and Strategic Transformation in Incumbent Organizations: A Systematic Literature Review - Dewayanto, Totok; Luhgiatno (STIE Pelita Nusantara Semarang, 2026)
Incumbent organizations face a paradox that digital-native ﬁrms do not: they must transform the very structures that made them viable in the ﬁrst place. This systematic literature review synthesizes 44 peer-reviewed sources across two analytical layers a PRISMA 2020 protocol covering Scopus (1990–2020), and a complementary thematic synthesis of literature published between 2014 and 2024 to map the mechanisms through which digital leadership drives strategic transformation in established ﬁrms. Three propositions, grounded in a Middle Range Theory (MRT) framework, organize the analysis: (1) co-creation strategy mediates the path from digital leadership to business model innovation, contingent on modular system architecture; (2) intellectual debate intensity between middle and top management determines whether organizations successfully traverse the